2011
DOI: 10.1111/j.1365-3091.2011.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Depositional processes, bedform development and hybrid bed formation in rapidly decelerated cohesive (mud–sand) sediment flows

Abstract: Flows with high suspended sediment concentrations are common in many sedimentary environments, and their flow properties may show a transitional behaviour between fully turbulent and quasi‐laminar plug flows. The characteristics of these transitional flows are known to be a function of both clay concentration and type, as well as the applied fluid stress, but so far the interaction of these transitional flows with a loose sediment bed has received little attention. Information on this type of interaction is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
276
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(292 citation statements)
references
References 41 publications
3
276
0
6
Order By: Relevance
“…In the Gottero case, the thicker event beds (>2 m) also have thick associated mudstone caps suggesting these flows carried significant clay loads, but these were deposited after the emplacement of the H3 divisions, possibly from ponded suspensions given that they are of similar thickness to the sandy lower part of the bed. The decelerating experimental flows examined by Baas et al (2011) were unable to separate clay and sand once the concentration of clay exceeded 12%, emplacing thick fluid mud layers (see also Sumner et al, 2009); the sandy mudstones that might be expected were clay-rich flows to have arrested in this manner are not seen in this study.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 48%
“…In the Gottero case, the thicker event beds (>2 m) also have thick associated mudstone caps suggesting these flows carried significant clay loads, but these were deposited after the emplacement of the H3 divisions, possibly from ponded suspensions given that they are of similar thickness to the sandy lower part of the bed. The decelerating experimental flows examined by Baas et al (2011) were unable to separate clay and sand once the concentration of clay exceeded 12%, emplacing thick fluid mud layers (see also Sumner et al, 2009); the sandy mudstones that might be expected were clay-rich flows to have arrested in this manner are not seen in this study.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 48%
“…Hybrid event beds (Haughton et al, 2003(Haughton et al, , 2009) are most commonly identified toward the bases and fringes of lobe deposits (e.g., Hodgson, 2009;Talling, 2013). However, they can form in any environment where mud and mudstone clasts are entrained into the turbulent flow, damping turbulence, and developing high-concentration to pseudo-laminar flow conditions (e.g., Ito, 2008;Haughton et al, 2003;Talling et al, 2004;Baas et al, 2011;Pierce et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, van Rijn (2006) replaced the factor 0.5 in Eq. (3) with a bedform shape factor, f, which has been shown to be approximately 0.6 for current ripples and dunes (van den Berg, 1987;Hoekstra et al, 2004;Baas et al, 2011). Eq.…”
Section: Bed Materials Transport Ratementioning
confidence: 99%